Allergic Bronchopulmonary Aspergillosis and Bronchial Asthma, A Forgotten Partners (Medical Forum Monthly, 2024)
Objective: To evaluate the incidence of ABPA (Allergic Broncho Pulmanary Aspergillosis) in Asthma.Study Design: Observational StudyPlace and Duration of Study: This study was conducted at Pulmonology Department, Bolan Medical College Quetta from 2005-2010.Materials and Methods: Forty Cases both male and female were included in this study. A detailed medical history, complete physical examination, recent posteroanteral and lateral chest X.Ray were obtained. Where ever possible previous X-Ray chest were also obtained for comparison and to see the fleeting shadows. Laboratory help included absolute eosinophil count, total serum IgE, Sputum for fungal hyphae and spirometry.Results: Among forty (40) cases 90 % were asthmatics between 11-40 years of age. In 92 % of cases the radiological findings were fleeting in nature. 70 % were misdiagnosed and treated as pulmonary tuberculosis. All 40 case had raised (70.5 x 109 perlitre) absolute eosinophil count in peripheral blood. Sputum eosinophilia was detected in 77 % of cases and fungal hyphae were isolated in 47 % cases bronchospy and serum IgE levels were also abnormal but performed in only 25% cases.Conclusion: ABPA must be considered in asthma patients having unexplained , fleeting or persistent chest radiographic shadows.